Bacterial Flocculation Of Phosphate Wastes Using A Hydrophobic Bacterium - R. W. Smith (The Minerals, Metals and Materials Society, 1992)
A microorganism will function as a mineral flocculant if it is to some degree hydrophobic and can attach itself in some manner, such as through electrostatic interaction, to the fine mineral particles to be flocculated. The present paper concerns the use of a hydrophobic bacterium, Mycobacterium phlei, as flocculating agent for phosphate slimes. Experimental work on the flocculation of phosphate slimes and of dolomite and clay mineral suspensions was performed. It was found that M. phlei functions as an excellent flocculant for a dolomitic slime but does not function as well for mineral suspensions where large quantities of the solids are finer in size than the approximately 1 µm size of the bacterium.